PENTOSAN POLYSULFATE-ASSOCIATED DYSPLASIA IN INFLAMMATORY BOWEL DISEASE: A CASE SERIES. (26th January 2023) - Anderson, Jenna; Frost, Spencer; Keyashian, Kian; Modiano, Nir
Abstract: BACKGROUND: Pentosan polysulfate is used for symptomatic management of interstitial cystitis. At one institution we incidentally noted six patients who were on this agent and had a diagnosis of inflammatory bowel disease (IBD). Three of these patients stopped the drug and all three had clinical and/or endoscopic improvement. Three of the six patients developed multifocal dysplasia. This observation led us to evaluate the hypothesis that pentosan polysulfate is associated with dysplasia in patients with IBD. METHODS: We searched the electronic medical records at two tertiary care centers to identify patients using pentosan polysulfate who had a diagnosis of Crohn's disease or ulcerative colitis. RESULTS: Thirty patients who met the search criteria were identified. Of these, 10 (33.3%) had colonic dysplasia: 8 (80%) with low-grade dysplasia and 2 (20%) with both low- and high-grade dysplasia. Of the patients with dysplasia, 6 (60%) required colectomy for endoscopically unresectable dysplasia. Following physician consultation, three patients (10%) discontinued the drug and subsequently demonstrated clinical benefit and/or achieved endoscopic healing. CONCLUSIONS: Inflammatory bowel disease patients at two institutions who had taken pentosan polysulfate had high rates of colonic dysplasia leading to surgery. Patients in this cohort who stopped this agent showed improvement in their colitis. These findings raise questions about whether pentosan polysulfate may play a causal role in both the development of colitis and the observed high rate of dysplasia. If larger studies validate these findings, this would indicate a readily identifiable subset of patients who are at high risk of developing colitis-associated malignancy.